Climate change and tectonic activity during the early Pliocene Warm Period from the ostracod record at Lake Qinghai, northeastern Tibetan Plateau. (1st May 2017) - Lu, Fengyan; An, Zhisheng; Chang, Hong; Dodson, John; Qiang, Xiaoke; Yan, Hong; Dong, Jibao; Song, Yougui; Fu, Chaofeng; Li, Xiangzhong
Highlights: A well age-constrained high-resolution ostracod record on the TP. Humid climate condition with variability during the EPWP in the Lake Qinghai area. Biological evidence for ASM evolution and TP tectonic activity in the Pliocene. The TP tectonic activities at ∼3.6 Ma is significant to environment changes. Abstract: The Early Pliocene Warm Period (EPWP, 5–3 Ma) is sometimes thought to be a useful analogue for a future warmer world, and thus the boundary conditions and drivers of climate in the EPWP may provide valuable lessons for understanding how a future warmer world might unfold. Lake Qinghai is located on the northeastern margin of the Tibetan Plateau (TP) and is affected by both Monsoon climate and Westerlies circulation. It is sensitive to the climate drivers of these systems. Its sediments, accumulated over the Cenozoic period, are a rich source of information for climate, tectonics and environmental changes of the period. We present a high-resolution ostracod record from a Lake Qinghai sediment core with a record of the period 5.10–2.60 Ma, thus covering the EPWP. Ostracods appear at 4.63 Ma and are most abundant until 3.58 Ma, while a body of water was present at the core site. This suggests a phase of humid climate and an intensified Asian Summer Monsoon (ASM), which is consistent with a warmer and wetter climate in the early Pliocene. Within this period the ostracod record shows some variabilities in lake level with deeper periods suggesting more intense ASM compared to those with shallower water. The disappearance of ostracods at 3.58 Ma may provide evidence for the uplift of Qinghai Nanshan (south of Qinghai Lake) since this is when the ASM intensified.